Nurses' Use of Research in Practice at Three US Army Hospitals - Deborah J. Kenny (Nursing Leadership, 2005)
Translation of research into clinical nursing practice has been extensively studied with nurses in civilian institutions. However, limited examination has been made of research utilization in US military facilities. A quantitative survey approach, using Estabrooks's adapted Research Utilization Survey and Mylle's Organizational Climate Survey, was employed to determine the extent that registered nurses in selected US Army Medical Treatment Facilities (MTFs) use research findings for their own practice and to describe the factors, both professional and organizational, that enhance or hinder research utilization. This study found that nurses at the MTFs reported using research in their practice less than half the time. Variables most significantly correlated with research utilization were belief suspension and attitudes toward research. The variable of support correlated significantly with all types of research utilization except indirect. Other organizational factors influencing nurses' use of research findings in practice were time, accessibility to research and a champion to assist their efforts. Interestingly, the number of years worked in nursing and in the facilities correlated inversely with research utilization, suggesting that over time, nurses may begin to rely on past experience rather than seek out new knowledge for practice.